Jewish national autonomy in Lithuania in 1919-1926th - Valkauskas, Raimundas (Lietuvos istorijos studijos, 1996)
After World War I, the problems of the racial, linguistic, and religious minorities were brought to the attention of the Peace Conference of Paris. The Jewish community, through a special delegation, demanded the recognition of the Jews as a "national minority" and brought their influence to protect and safeguard the rights of Jews.The Declaration of Independence (February 16, 1918) was the first step towards the restoration of Lithuanian statehood. The Jews of Lithuania took an active part in the process of Lithuania's international recognition.The representatives of the Lithuanian governmental delegation at the Peace Conference signed the letter-declaration (August 5, 1919), containing the obligation to respect and guarantee the rights of the Jews: complete equality before the law; the free use of their own language; the rights to control their own religious, educational, and social institutions; and an equitable share of public funds allotted to educational, religious, or charitable purposes.This declaration and another law (The Temporary Law About the Rights of Jewish Communities, January 10, 1920) accepted by the Lithuanian Government was the legal foundation that created Jewish national autonomy in Lithuania. The structures of this autonomy—the Jewish communities and their Councils, the Jewish National Council, and the Ministry of Jewish Affairs—had been tolerated by the Lithuanian political parties until the end of 1922.The new Constitution of Lithuania was accepted in August 1922, but it didn't establish the structures of Jewish national autonomy, only the general rights of the minorities of Lithuania.The Christian Democratic Party and its representatives in the Seimas extended their influence over the state's power and were not satisfied with the Jews still dominating in the economy of the land. Shortly after this, when the Jewish representatives in the Seimas refused to support the aims of the Christian Democrats (the end of 1922), more and more anti-Semitic manifestations took place in public life and in the pages of newspapers. The previous structure of the Jewish national autonomy was abolished by the political decisions of the Lithuanian Christian Democratic Party in 1923–1925.
Keywords: -